2022
DOI: 10.1007/s12012-022-09730-0
|View full text |Cite
|
Sign up to set email alerts
|

AT1 Receptors: Their Actions from Hypertension to Cognitive Impairment

Abstract: Hypertension is one of the most prevalent cardiovascular disorders worldwide, affecting 1.13 billion people, or 14% of the global population. Hypertension is the single biggest risk factor for cerebrovascular dysfunction. According to the American Heart Association, high blood pressure (BP), especially in middle-aged individuals (~ 40 to 60 years old), is associated with an increased risk of dementia, later in life. Alzheimer’s disease and cerebrovascular disease are the two leading causes of dementia, account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 123 publications
(133 reference statements)
0
15
0
Order By: Relevance
“…Exposure to indoxyl sulfate significantly increased the expression of angiotensinogen protein in human proximal tubular cells (HK-2) and rat renal cortex, thus leading to RAS activation and the generation of Ang II peptides [168]. In the brain, Ang II increases the production of vasopressin and induces vasoconstriction by activating the angiotensin II type 1 receptor (AT1R) [169][170][171]. Zhang et al [172] demonstrated in mice that an infusion of Ang II for two weeks induced cerebral microvascular inflammation and increased the permeability of mouse BBB.…”
Section: Ahr Signaling Controls Blood Flow In Brain Via Renin-angiote...mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to indoxyl sulfate significantly increased the expression of angiotensinogen protein in human proximal tubular cells (HK-2) and rat renal cortex, thus leading to RAS activation and the generation of Ang II peptides [168]. In the brain, Ang II increases the production of vasopressin and induces vasoconstriction by activating the angiotensin II type 1 receptor (AT1R) [169][170][171]. Zhang et al [172] demonstrated in mice that an infusion of Ang II for two weeks induced cerebral microvascular inflammation and increased the permeability of mouse BBB.…”
Section: Ahr Signaling Controls Blood Flow In Brain Via Renin-angiote...mentioning
confidence: 99%
“…It is known that Ang II peptide can also activate AT2R and Mas receptor (MasR) which display counteracting effects to the AT1R, i.e., they promote vasodilation, decrease blood pressure, and stimulate responses against inflammation and fibrosis [171]. Post-mortem studies on AD brains have revealed that the expression levels of AhR, Ang II, and AT1R proteins were significantly increased, whereas that of MasR protein was clearly down-regulated in hippocampus samples [10,177].…”
Section: Ahr Signaling Controls Blood Flow In Brain Via Renin-angiote...mentioning
confidence: 99%
“…Ubiquitous actions of the main effector of the RAS, namely Ang II, are related to the activation of several signal transduction pathways, which are predominantly attributed to the Ang II type 1 receptor (AT 1 R). In addition, Ang II also acts through the Ang II type 2 receptor (AT 2 R), or is degraded by ACE2 to Ang 1-7 acting via the Mas receptor (MasR) [ 27 , 28 ]. All receptors are GPCRs; for details of the most important signaling pathways of AT 1 Rs, see Section 3.2.1 .…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of ACE leads to the hyperactivation of AT1R by Ang II, conducting to brain vasoconstriction associated with cognitive impairment, cell death, and inflammation (Labandeira-Garcia et al, 2017). AT1R promotes inflammation by the secretion of proinflammatory cytokines and the activation of microglia; this activation also produces oxidative stress that activates programmed cell death in specific regions with cognition functions such as the cortex and hippocampus, conducing to cognition impairment (Wu et al, 2022; Figure 1). These effects are due to the increment in the ROS by the induction of NADPH oxidase 2 (NOX2) and NOX4 axes (Peng et al, 2013).…”
Section: Local Brain Renin-angiotensin Systemmentioning
confidence: 99%